A FEMALE WITH MALIGNANT ASCITES: A DIFFICULT CASE WITH CARCINOMA OF UNKNOWN PRIMARY - Retno W, Dyah; -, Supriono (journal of internal medicine, 2012)
Malignant ascites is the abnormal accumulation of !uid in the peritoneal cavity associated with several intra-pelvicand intra-abdominal malignancies. Among the gynecologic malignancies, ovarian carcinoma predominates. Of thegastrointestinal malignancies, ascites can occur with advanced colon, pancreas, gastric carcinoma, and esophagealcarcinoma. Recent reports in the cytological literature suggest that 6% to 11% of malignant peritoneal effusions aredue to tumors of unknown origin.1 We reported a 62 years old female presenting adenocarcinoma ascites, which shownconfusing of site of primary origin from imaging examination. First ultrasound imaging showed mass on colon area, butre ultrasound of abdominal imaging showed the possibility of endometrium carcinoma. The CA 125 level was high (2.294u/ml). Open laparotomy showed milliar metastatic several nodule on omental, liver, and abdominal wall. There wasattachment of vesica urinaria, endometrium, colon, sigmoid, and rectum. All those result conclude this patient sufferedfrom malignant ascites of adenocarcinoma of unknown primary origin, with highly suggestive from malignant ascites ofadenocarcinoma of unknown primary origin, with highly suggestive from gynecologic malignancy that difcult to differwhether from ovarian cancer or endometrium cancer. Somehow, the epidemiology, pathophysiology, clinical presentationlead the diagnosis for ovarian cancer.